The Superhumanities: Historical Precedents, Moral Objections, New Realities - Kripal, Jeffrey J. (The University of Chicago Press, 2022)
Intro -- Contents -- Prologue. Teaching the Superman -- Introduction. How the Book Came to Be -- 1. Legitimate Science Fiction: From the History of Religions to the Superhumanities -- 2. "The Truth Must Be Depressing": Immunological Responses of the Intellectual Body -- 3. The Human as Two: Toward an Apophatic Anthropology -- 4. Theory as Two: Rewriting the Real -- Conclusion. The Solid Rock Was Once Flowing -- Epilogue. Phoenix Rising -- Acknowledgments and the Sigil -- Notes -- Index.